Pengelolaan lembaga kearsipan di kantor surat kabar berita pagi Palembang - atika Putri (UIN Sumatera Utara, 2018)
This article discusses the management of archival institutions in the Palembang morning news paper office. The purpose of this paper is to find out the position of the structural side of the archive processing unit, and the archive management system and archive storage system at the Palembang Morning News Office. Data was obtained through direct observation of interviews with archival processing staff at the Palembang Morning News Office. The office implements a decentralized system which means that in each work unit it stores archives in their respective fields. And the conclusion in the Morning News Agency in Palembang was that there was no archival processing unit specifically processing the archives in the office, but they processed the archives in their respective work divisions in the office itself, while processing the archives themselves directly in their respective divisions. As well as archive storage managed through a date system. Keywords: filing unit, archive management, archive storage